Pengaruh Likuiditas Dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Manufaktur Subsektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Melfia Melfia; Mike Kusuma Dewi (Universitas 45 Surabaya, 2023)
This study is entitled The Effect of Liquidity and Company Size on Profitability in Manufacturing Companies in the Pharmaceutical Subsector Listed on the Indonesia Stock Exchange in 2017-2021. The formulation of the problem in this study is how the influence of liquidity and company size on profitability. This study aims to empirically analyze the effect of liquidity and firm size on profitability. The population in this study are Manufacturing Companies in the Pharmaceutical Subsector Listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method of determining the sample in this study uses a purposive sampling method, and based on the specified criteria, the number of samples is 8 companies. The data source in this study is secondary data obtained from the annual financial reports of companies listed on the Indonesia Stock Exchange for the 2017-2021 period by accessing www.idx.co.id. The analysis technique used is multiple linear regression analysis with the Eviews application tool. The results of this study indicate that Liquidity has a significant positive effect on profitability, and firm size has a significant negative effect on profitability.